1998
DOI: 10.2527/1998.762542x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of protein and lysine supply on performance, nitrogen balance, and body composition changes of sows during lactation.

Abstract: Using 73 Large White gilts, we studied the lysine requirement during lactation. Sow and pig performance and nitrogen balance of sows were measured during the total 21-d lactation period. Variation in body composition of sows between farrowing and weaning was determined by the comparative slaughter technique. Two levels of crude protein (15.5 and 17.1%) were combined with two levels of L-lysine HCl supplementation (0 and .16%), resulting in four diets termed P1L1, P1L2, P2L2, and P2L3, containing .66, .77, .77,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
79
4
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 110 publications
(99 citation statements)
references
References 20 publications
13
79
4
3
Order By: Relevance
“…Test of accuracy of the model The k lys was set to 0.80 after comparing the model prediction of SID lysine requirement and six studies (King et al, 1993;Coma et al, 1996;Dourmad et al, 1998a;Sauber et al, 1998;Yang et al, 2000;Huang et al, 2013; Figure 2). The k lys at 0.80 was consistent with what was derived from the InraPorc model (Dourmad et al, 2008), but was higher than the efficiency reported by NRC (2012), possibly due to the method used to obtain milk yield data.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Test of accuracy of the model The k lys was set to 0.80 after comparing the model prediction of SID lysine requirement and six studies (King et al, 1993;Coma et al, 1996;Dourmad et al, 1998a;Sauber et al, 1998;Yang et al, 2000;Huang et al, 2013; Figure 2). The k lys at 0.80 was consistent with what was derived from the InraPorc model (Dourmad et al, 2008), but was higher than the efficiency reported by NRC (2012), possibly due to the method used to obtain milk yield data.…”
Section: Resultsmentioning
confidence: 99%
“…A literature survey on body and mobilized body tissue composition in lactating sows (Dourmad et al, 1998a;Sauber et al, 1998;Jones and Stahly, 1999;McNamara and Pettigrew, 2002;Gill, 2006) showed that the sow mobilizes both fat and protein, although the protein requirement has been met by the diet. The calculated dietary protein requirement should cover the AA requirement for maintenance and milk production, as excessive mobilization from muscle protein is not desired because of the effects on subsequent reproductive performance (e.g.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations